The films of Ingmar Bergman Jesse Kalin. - Kalin, Jesse, 1940- (Cambridge film classics., 2003)
This volume provides a concise overview of the career of one of the modern masters of world cinema. Jesse Kalin defines Bergman's conception of the human condition as a struggle to find meaning in life as it is played out. For Bergman, meaning is achieved independently of any moral absolute and is the result of a process of self-examination. Six existential themes are explored repeatedly in Bergman's films: judgment, abandonment, suffering, shame, a visionary picture, and above all, turning toward or away from others. Kalin examines how Bergman examines these themes cinematically, through close analysis of eight films: well known favorites such as Wild Strawberries, The Seventh Seal, Smiles of a Summer Night, and Fanny and Alexander; and important but lesser known works, such as Naked Night, Shame, Cries and Whispers, and Scenes from a Marriage.